THE CONSERVATION OF PLANT GENETIC RESOURCES FOR FOOD AND AGRICULTURE: CONSUMERS’ PERSPECTIVES ANALYSIS IN SIBIU AGRI-FOOD MARKETS - Camelia SAND SAVA; Maria-Mihaela ANTOFIE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Agri-food markets are among the major pillars relevant for selling agri-food products. However, food industry and hospitality are among the major stakeholders in the food – chain economy. The connectivity between producers, sellers and consumers such as customers of agri-food markets, retailers, food industry and hospitality are relevant for assessing the future implementation of a feasible strategy regarding the rural sustainable development including the conservation of genetic resources for food and agriculture. Sibiu county is awarded for 2019 as a European Region of Gastronomy and therefore a major attention should be paid to city agri-food markets that should be oriented to local products selling. Sellers are among the relevant stakeholders to provide valuable information regarding the food-chain. The scope of this article is to assess the sellers from the largest agri-food market of Sibiu city: “Cibin” market. Based on this analysis, native products from Sibiu are replaced with similar products from different counties or from import to a share up to 5% even during the harvesting season. However, there is optimism in developing the preservation conditions for more perishable agri-food products that may further improve the selling of local products and as a consequence the maintenance of local resources. Thus, by developing preservation conditions for agri-food products will fuel the appropriate conservation measures implementation of plant genetic resources for food and agriculture in a most cost-efficient way.